ANALISA STATUS KEPEMILIKAN BARANG PENINGGALAN SANTRI BOYONG PERSPEKTIF HUKUM EKONOMI SYARI’AH - Ferdi Yogi Saputra; Wiwik Damayanti; Ita Dwilestari (KASBANA, 2025)
The phenomenon of unclear ownership status of inherited items from Islamic boarding schools (pesantren) often leads to ownership conflicts, especially when the items are reclaimed after a long time. This study aims to analyze the legal status of ownership of inherited items from Islamic boarding schools (pesantren) in Al-Qur'aniyy, Gajah City, Central Lampung, from the perspective of Islamic economic law. This study uses a qualitative method with a normative approach, through observation, interviews, and documentation techniques. The results show that items left by students remain private property until a valid contract is made in the form of a gift or wadi'ah. However, in practice, many students do not explicitly convey their intention to own, so that the pillars of the contract, such as ijab and qabul, are not fulfilled. The implication of this ambiguity is the potential for violations of ownership rights and misuse of assets. Therefore, written administrative policies and education related to Islamic contracts are needed to ensure the clarity of the status of items and realize the principle of Hifzh al-Mal in the maqashid sharia. Keywords: Grants, Sharia Economic Law, Ownership, Wadi'ah